A new species of Atractus Wagler, 1828 (Serpentes: Colubridae) from Eastern Amazonia, Brazil - Prudente, Ana L.d.c.; Santos-Costa, Maria C. Dos (Zootaxa, 2006)
A new species of Atractus from the “Estação Científica Ferreira Penna”, Eastern Amazonia, Pará State, Brazil is described, and diagnosed by the following set of characters: 17-17-17 smooth dorsal scales without pits; 162 ventrals and 30 pairs of subcaudals in the single measurable male and 171 ventrals and 24 pairs of subcaudals in the single avaliable female; the three available specimens (two males and one female) has frontal wider than long; nasal contacting loreal, internasals, rostral, and the two first pairs of supralabials; loreal contacting internasal, and second and third supralabials; preocular absent; two postoculars; two light spots on the back of the head; wide-black median ventral band; and subcaudals totally black.